DECENTRALIZATION OF EDUCATION THROUGH SCHOOL/MADRASAH BASED MANAGEMENT (MBS/M) - Muhammad Syam; Muhammad Abdillah Khairi; Muhammad Abdurrahman Rahim; Abdurrahman Abdurrahman; Mujhirul Iman (Yayasan Amanah Nur Aman, 2026)
Decentralization of education through School/Madrasah-Based Management (SBM/M) is a strategy to improve the quality of education by granting schools or madrasas broader authority in managing resources, developing programs, and making decisions according to the needs and characteristics of each institution. This article aims to examine the concept, implementation, and impact of SBM/M implementation in supporting the effectiveness of education management. The study uses a library research method by analyzing various scientific literature, books, and relevant regulations. The results of the study indicate that the implementation of SBM/M can increase school community participation, management transparency, accountability, and the quality of education services when supported by effective leadership, human resource competency, and community involvement. Thus, decentralization of education through SBM/M is a strategic approach in realizing independent, democratic education governance, and oriented towards continuous quality improvement.